2022
DOI: 10.3389/fneur.2022.895638
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Effects of Resecting Skull Base Tumors Using Pre-operative Multimodal Image Fusion Technology: A Retrospective Study

Abstract: ObjectivesTo analyze the surgical effects of resecting skull base tumors using multimodal three-dimensional (3D) image fusion technology in the neurosurgery department and present some typical cases.MethodsFrom October 2019 to October 2021, we included 47 consecutive patients with skull base tumors in the Neurosurgery Department at Zhuhai People's Hospital in this study. Pre-operative head computed tomography and magnetic resonance imaging data acquisition was performed using the GE AW workstation software for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The latest research in the past mainly applied 3D visualization technology to preoperative planning of intracranial lesions and liver tumors [13][14][15][16][17][18][19],Through the 3D visualization technology, a 3D stereo model is constructed, and the size, specific location of the tumor and the anatomical relationship between the tumor and the surrounding adjacent tissues can be observed more intuitively [20,21], so that a fine surgical path can be formulated, which is similar to the content of this study. In all cases in this study, patients with giant goiter had varying degrees of tracheal compression, displacement, malformation, or luminal stenosis, which may make intraoperative anesthetic intubation difficult.…”
Section: Discussionmentioning
confidence: 81%
“…The latest research in the past mainly applied 3D visualization technology to preoperative planning of intracranial lesions and liver tumors [13][14][15][16][17][18][19],Through the 3D visualization technology, a 3D stereo model is constructed, and the size, specific location of the tumor and the anatomical relationship between the tumor and the surrounding adjacent tissues can be observed more intuitively [20,21], so that a fine surgical path can be formulated, which is similar to the content of this study. In all cases in this study, patients with giant goiter had varying degrees of tracheal compression, displacement, malformation, or luminal stenosis, which may make intraoperative anesthetic intubation difficult.…”
Section: Discussionmentioning
confidence: 81%
“…In recent years, a similar technology, multimodal image fusion (MIF), has also been proposed to assist surgery. Jian et al evaluated the usefulness of MIF in a total of 47 skull base tumor cases and acknowledged the outstanding performance of MIF [ 28 ]. Despite the towering case number, in this study, assessment of the fused 3D images was conducted by only one person, the operating surgeon, which undermines the credibility of the research.…”
Section: Discussionmentioning
confidence: 99%
“…A specific and comprehensive preoperative evaluation with multiple image fusion was of great benefit. 11 This report summarizes our experience in 7 cases of complex skull base tumors from October 2019 to January 2022.…”
mentioning
confidence: 94%
“…Oishi et al 10 study revealed that preoperative multimodal image fusion could assist the neurosurgeon to design a more reasonable bone window and a safe approach. A specific and comprehensive preoperative evaluation with multiple image fusion was of great benefit 11 . This report summarizes our experience in 7 cases of complex skull base tumors from October 2019 to January 2022.…”
mentioning
confidence: 97%